2018
DOI: 10.1159/000492391
|View full text |Cite
|
Sign up to set email alerts
|

Uveal Melanoma in Ireland

Abstract: Purpose: To report the clinical features and epidemiology of uveal melanoma in Ireland. Methods: This was an observational study of 253 patients with a new diagnosis of uveal melanoma between June 2010 and December 2015. Main outcome measures included demographics, clinical features, age-adjusted incidence, relative survival, overall survival, and distant metastases-free survival. Results: The mean patient age was 61.7 years. Tumour location was choroidal in 82%, ciliochoroidal in 9%, iridociliary in 2%, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 51 publications
5
25
0
Order By: Relevance
“…A further, larger, study performed in a population comparable to Scotland's would be of clinical value to ascertain whether there is geographical variation in UM prognosis, or possibly, whether the overall prognosis of UM is improving. A recently published study by Baily et al reports another discrete stable population-the neighbouring Republic of Irelandwhich describes a similar epidemiology of UM, since the establishment of their dedicated ocular oncology service in 2010 [28]. Survival rates have been calculated to four years (88% overall cancer-specific survival, 95% CI:82-93) and longer follow-up will allow comparison of survival outcomes with this centre, and hopefully others, in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…A further, larger, study performed in a population comparable to Scotland's would be of clinical value to ascertain whether there is geographical variation in UM prognosis, or possibly, whether the overall prognosis of UM is improving. A recently published study by Baily et al reports another discrete stable population-the neighbouring Republic of Irelandwhich describes a similar epidemiology of UM, since the establishment of their dedicated ocular oncology service in 2010 [28]. Survival rates have been calculated to four years (88% overall cancer-specific survival, 95% CI:82-93) and longer follow-up will allow comparison of survival outcomes with this centre, and hopefully others, in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of melanocytes and melanoma cells from light-coloured and dark-coloured irises found that while the melanoma cells shared approximately the same pheomelanin levels as their melanocyte counterparts, UM cells had only 1/8th and 1/31st the eumelanin levels that were in the counterpart melanocytes from eyes with light-coloured irises and dark-coloured irides respectively [ 68 ]. Differences in melanin quality in uveal melanocytes could be why populations with very high proportions of Caucasians–an ethnicity generally characterised by light skin and eyes–have much higher incidence of UM than darker ethnicities [ 25 , 26 ]. However, it has also been suggested that light-coloured eyes may have an increased susceptibility to the light spectrum, rather than UVR [ 69 ], which could be driving this increase in UM incidence (see Section 6.1 ).…”
Section: Interactions Between Uvr and The Eyementioning
confidence: 99%
“…It has an incidence of only 5 to 10 per million per year in Australia [ 21 ] compared to nearly 500 cases of CM per million per year [ 15 ]. Regardless, the incidence of UM in Australia is still high compared to Canada (3.75 per million) [ 22 ] and the United States (5 per million) [ 23 , 24 ], and is matched only by countries with very high proportions of UVR-susceptible ethnicities (but not necessarily high UVR exposure) such as Denmark (8.6 per million) [ 25 ] and Ireland (9.5 per million) [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, in 2019, an observational study was published about the incidence of UM in Ireland. Ireland had not been included in the study by the EUROCARE workgroup, and the mean age-adjusted incidence of UM in Ireland was 9.5 per million, which is higher than in any of the countries involved in the EUROCARE study [ 38 ]. An explanation could be that risk factors of UM such as light skin colour, light hair colour and light eye colour are stereotypical traits of the native Irish population [ 16 , 18 , 36 , 37 ].…”
Section: Incidencementioning
confidence: 99%